Quality of Private Investment Licensing Services at the Investment and One-Stop Integrated Services Office in Bima City - Azhar Permana (FKIP, Universitas Palangka Raya, 2023)
The integrated investment and licensing agency office is a technical organization for licensing and non-licensing services in South Sulawesi Province which was formed based on Bulukumba Regency regional regulations. This is done as a follow-up to improve the smooth running of general tasks in the field of licensing and more successful implementation of public services in practice. The One-Stop Investment and Licensing Agency or in short BPMPT BIMA CITY is a combination of the capital investment agency and the integrated licensing service office which was established in 2016. Reporting from the website www.lapor.go.id that there are unqualified services at the Bima City One-Stop Investment and Integrated Service Office related to managing trade business licenses, namely the length of the process of completing a Trade Business License (SIUP) for more than 2 months, even though the completion time is only 14 working days. In addition, it was reported from the website http://dpmptsp.pemkomedan.go.id that there are still those who take care of their trade business licenses through brokers or service bureaus, which means that it is difficult to take care of trade business licenses at the DPMPTSP of Bima City